Implementation Of Benson Relaxation Technique In Nursing Care For Patients With Unstable Angina Pectoris - Rafika Nur Siregar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
One of the cardiovascular diseases that can cause death is Unstable Angina Pectoris (UAP) Benson relaxation is a passive relaxation technique without using muscle tension so it is very appropriate to reduce pain. Benson relaxation is a development of the relaxation response method by involving the patient's belief factor, which can create a calm internal environment that can help patients achieve higher health and well-being. Method:Descriptive method in the form of case studies. Nursing care approach consisting of from assessment, nursing diagnosis, planning, implementation, evaluation and documentation nursing. The subject of this study was one person. Results:Benson relaxation is a passive relaxation technique without using muscle tension so it is very appropriate to reduce pain. Conclusion: Benson Relaxation therapy in patients with Unstable Angina Pectoris (UAP) was carried out for 3 days. It was found that there was a decrease in the pain scale. This is evidenced by the results of the evaluation on the first day, March 1, 2024, the pain scale was 7 to 7. The second day, March 2, 2024, the pain scale was 7 to 5. The third day, March 3, 2024, the pain scale was 5 to 3.